A study on the factors that influence employers perception on graduate employability and marketability in public university in Bandaraya Melaka / Noor Umizatul Nabila Mohd Fadzil and Nor Hasmihah Abd Talib - Mohd Fadzil, Noor Umizatul Nabila; Abd Talib, Nor Hasmihah (Faculty of Administrative Science and Policy Studies, 2014)
In this challenging world, competition is everywhere. Individual need to work hard in order to equip themselves with knowledge and skills to avoid from being left far behind and survive. However, the issue of unemployment among graduates in Malaysia which is at a critical level. The Deputy Human Resource Minister Datuk Maznah told Parliament that in 2012 some 76,200 graduates in the country were unemployed. The aim of this study is to discover the factors that influence employers perception on graduate Employability and Marketability in Public University in Malaysia as well as look for the qualities of a graduate that an employer looking for. The questionnaires were distributed to the employers from public and private company in Bandaraya Melaka. The sample size of the respondents is 40. The technique used in this study is central tendency, inferential and spearman rank correlation. The sampling technique used is nonprobability sampling which is convenience sampling. Besides, this paper also study the company needs for future graduates and suggest some measures that public university should take into consideration in order to meet the needs of employers.